Analisis Kinerja Keuangan terhadap Harga Pasar Saham pada Perusahan Pembiayaan Terbuka - Siagian, Pariang (Bina Nusantara University, 2014)
The main purpose of this article is to inform the result of research and analysis of financial performace effects to the stock market price done to go public financing companies in 2008-2012. Financial performance was assessed based on annual financial statements published on the website of each company and stock market price from the Stock Exchangeâs website by the end of research period. Analysis of the financial performance limited on four financial ratios as representation of its financial ratios, such Current Ratio, Asset Turn Over, Return On Asset, and Debt Ratio. From the research and analysis obtained, there are significant effects from various independent variables to dependend variable, with t value: Current Ratio 0,738, Asset Turn Over 0,121, Return On Asset 0,703, and Debt Ratio 0,374; likewise simultaneously test with F value 0,41. All values showed more than 0,05; that it can be concluded there are significant effects between each independent variable and simultaneously to the dependent variable.